Letter: repeat hepatic resection versus radiofrequency ablation for recurrent hepatocellular carcinoma in ideal candidates. Issue 7 (13th March 2023) - Teng, Yu‐Xian; Zhang, Wan‐Guang; Chan, Anthony Wing‐hung; Chong, Charing Ching Ning; Serenari, Matteo; Wang, Yan‐Yan; Peng, Ning; Huang, Tao; Lu, Shi‐Dong; Liang, Zhi‐Yin; Ma, Liang; Zhong, Jian‐Hong
LINKED CONTENT: This article is linked to Tong et al papers. To view these articles, visit https://doi.org/10.1111/apt.17263 and https://doi.org/10.1111/apt.17423